2020
DOI: 10.1681/asn.2020010081
|View full text |Cite
|
Sign up to set email alerts
|

A Land of Controversy: Fibroblast Growth Factor-23 and Uremic Cardiac Hypertrophy

Abstract: Cardiac hypertrophy is a common feature in patients with CKD. Recent studies revealed that two phosphate regulators, fibroblast growth factor-23 and α-Klotho, are highly involved in the pathophysiologic process of CKD-induced cardiac hypertrophy. With decreasing renal function, elevated fibroblast growth factor-23 and decreased α-Klotho may contribute to cardiac hypertrophy by targeting the heart directly or by inducing systemic changes, such as vascular injury, hemodynamic disorders, and inflammation. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 127 publications
0
10
0
Order By: Relevance
“…Later, CKD-MBD was considered a cardiovascular risk factor, and vitamin D and FGF-23 have gained wide concern ( 26 ) (Cluster ID #5, ID #7, and ID #19, Figure 5A ), especially FGF-23 was found to correlate to LVH and can directly induce LVH ( 12 , 27 ). In recent years, the hotspot of uremic cardiomyopathy was on “klotho” (Cluster ID #3, Figure 5A ), which declines CKD and has FGF-23-dependent and FGF-23-independent protective effects on the myocardium ( 28 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, CKD-MBD was considered a cardiovascular risk factor, and vitamin D and FGF-23 have gained wide concern ( 26 ) (Cluster ID #5, ID #7, and ID #19, Figure 5A ), especially FGF-23 was found to correlate to LVH and can directly induce LVH ( 12 , 27 ). In recent years, the hotspot of uremic cardiomyopathy was on “klotho” (Cluster ID #3, Figure 5A ), which declines CKD and has FGF-23-dependent and FGF-23-independent protective effects on the myocardium ( 28 ).…”
Section: Resultsmentioning
confidence: 99%
“…Most recent progress on uremic cardiomyopathy is mainly based on studies performed by Hu et al ( 29 ) and Leifheit-Nestler et al ( 30 ), who found that soluble klotho can alleviate LVH in CKD. Further investigations found the protective effects of soluble klotho are FGF-23-dependent and FGF-23-independent ( 28 ), thus, implying another therapeutic strategy for uremic cardiomyopathy ( Figures 5A , 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…High FGF23 in plasma has been linked to a higher risk of cardiovascular disease, all‐cause mortality, infection, and inflammation 4 . Although the direct effect of FGF23 is still under debate, at least for cardiac hypertrophy, the fact is that high FGF23 levels are observed under stress states 1,5 . In addition to calcitriol and PTH, calcium, iron, inflammatory factors, hypoxia, erythropoietin (EPO), extracellular volume, and leptin have recently emerged as regulators of FGF23 1,6 …”
Section: Introductionmentioning
confidence: 99%
“…Fibroblast growth factor 23 is considered to be a major contributor to the development of LVH, heart failure, atrial fibrillation, and increased cardiovascular and all-cause mortality in CKD (Faul et al, 2011;Kendrick et al, 2011;Scialla et al, 2014;Mehta et al, 2016) and non-CKD (Ix et al, 2012;Kestenbaum et al, 2014;Lutsey et al, 2014) populations. However, it is still intensively discussed whether elevated FGF23 is cardiotoxic per se (Marthi et al, 2018;Pastor-Arroyo et al, 2018;Zhou et al, 2018;Bao et al, 2020). All previously reported animal models developing LVH in the presence of elevated circulating Fgf23 levels due to experimental uremia, genetic deletion of klotho, high phosphate diet, or injection of recombinant FGF23 protein display a variety of systemic changes that are all proven contributors to cardiac injury, making it difficult to elucidate the causative role of FGF23 for LVH in these studies (Faul et al, 2011;Andrukhova et al, 2014;Grabner et al, 2015; Yang et al, 2015;Leifheit-Nestler et al, 2017).…”
Section: Discussionmentioning
confidence: 99%